RESIPROSITAS DI KALANGAN PELAJAR KOTA LARANTUKA: INSPIRASI MODERASI BERAGAMA BAGI KAUM MUDA - Dominikus Doni Ola; Anselmus D. Atasoge (Lumen: Jurnal Pendidikan Agama Katekese dan Pastoral, 2022)
In essence, every religion wants its adherents to live peacefully in the midst of religious and cultural diversity. However, this hope does not always materialize in the construction of real life on Indonesian soil with the presence of inter-religious and inter-ethnic conflicts. Conflict experiences become endless lessons as an effort to maintain peace and harmony in religious life. A number of local praxis and initiatives were raised to untangle the tangled threads of inter-religious conflicts in Indonesia by prioritizing a balanced way of religious life that does not view others as opponents. This study of reciprocity in relation to religious moderation originates from the local context of Larantuka and draws its relevance to efforts to inculcate religious moderation in Indonesia. In a more specific context, the focus of this study is to describe the practical life of religious communities in the city of Larantuka, East Flores, East Nusa Tenggara which can be seen as the foundation and medium for grounding the ideals of religious moderation in Indonesia. The praxis of life in question is the reciprocity of young students in the city of Larantuka both within the school environment and among people who have different religious and ethnic backgrounds. Therefore, the basic question is how reciprocity among students in the city of Larantuka can become an inspiration and basis for efforts to instill religious moderation.